A novel flexible conductive sponge-like electrode capable of generating electrical energy from the direct oxidation of aqueous glucose. (November 2019) - Desmaële, D; La Malfa, F; Rizzi, F; Qualtieri, A; Di Lorenzo, M; De Vittorio, M
Abstract: This paper presents a new sponge-like electrode (SLE) material structured with porous gold (PG). The fabrication process is simple and no specific equipment is required. Notably, the use of liquid metal particles enables the direct growth of PG into the pores of a flexible conductive support matrix. With a SLE sample 13 mm long, 6 mm wide and 1.5 mm thick immersed in a 10 mM glucose solution, we demonstrate that a volumetric power density of 2.4 mW · cm −3 at ≈ 5 mA · cm −3 and 0.48 V can be reached without using any enzymes. Because the process presented is versatile and scalable, we envision SLEs with long-term stability that could to meet the power budget of various wearable/bioelectronic devices.